2019
DOI: 10.1002/jcp.28204
|View full text |Cite
|
Sign up to set email alerts
|

A detailed image of rutin underlying intracellular signaling pathways in human SW480 colorectal cancer cells based on miRNAs‐lncRNAs‐mRNAs‐TFs interactions

Abstract: Natural dietary ingredients like flavonoids are important for body improvement against diseases. The flavonol rutin is widely found in fruits and vegetables and shows significant anticancer properties. However, the underlined signaling pathways have not been elucidated yet. In this study, the impacts of various doses of rutin (400–700 mM/ml) have been examined on human colon cancer SW480 cells metabolism, cell cycle, and apoptosis. The transcriptome was analyzed by bioinformatics tools and the interactions bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…Metabolic activities of the cells were reducing, the population was halved and the cell cycle was ceased at the sub-G1 phase when rutin was applied. According to the enriching analyses of miRNAs-lncRNAs-mRNAs-TFs network, altering glucose, lipid, and protein metabolism led to mediation of the impacts, while endoplasmic reticulum stress reactions were modulated, the cell cycles processes were negatively regulated, and the internal as well as external apoptotic signaling pathways were induced (Nasri Nasrabadi et al, 2019).…”
Section: Mirnas-lncrnas-mrnas-tfs Interactionsmentioning
confidence: 99%
“…Metabolic activities of the cells were reducing, the population was halved and the cell cycle was ceased at the sub-G1 phase when rutin was applied. According to the enriching analyses of miRNAs-lncRNAs-mRNAs-TFs network, altering glucose, lipid, and protein metabolism led to mediation of the impacts, while endoplasmic reticulum stress reactions were modulated, the cell cycles processes were negatively regulated, and the internal as well as external apoptotic signaling pathways were induced (Nasri Nasrabadi et al, 2019).…”
Section: Mirnas-lncrnas-mrnas-tfs Interactionsmentioning
confidence: 99%
“…The results showed that the cell metabolism activity was significantly reduced, and the cell cycle was inhibited below G1 phase in rutintreated cells. Enrichment analysis of the miRNAs-lncRNAs-mRNAs-TFs network showed that these effects were mediated by changes in glucose, lipid, and protein metabolism, regulation of endoplasmic reticulum stress response, negative regulation of cell cycle processes, and induction of intracellular and extracellular apoptotic signaling pathways (Nasri Nasrabadi et al, 2019). Zhao et al found that Celastrol alleviated cholestatic liver injury in mice through activation of sirtuin 1 (SIRT1), increasing the farnesoid X receptor (FXR) signaling pathway, and inhibiting the nuclear factorkappa B (NF-kB) and P53 signaling pathways by RNA-seq technology (Zhao et al, 2019).…”
Section: Rna-seq In Identification Of Drug-target Genes and Drug Re-pmentioning
confidence: 99%
“…Rutin ameliorates the metabolism of colon cancer SW480 cells, increases apoptosis, and arrests the cell cycle at the sub-G1 phase. Analysis of microRNAs, long noncoding RNAs, messenger RNAs, and transcription factors revealed that these promising effects were associated with the modulation of dysregulated intracellular signaling pathways involved in glucose, lipid, and protein metabolism, extrinsic and intrinsic apoptosis, reticulum stress responses, and cell cycle stages [ 120 ]. Future studies should investigate the proposed panel in other cancer models.…”
Section: Anticancer Activities Of Rutinmentioning
confidence: 99%